Remarks by World Bank Group President David Malpass to G20 Finance Ministers and Central Bank Governors on the Global Economy and Health Agenda - Malpass, David (World Bank, Washington, DC, 2022)
These opening remarks were made by World Bank Group President David Malpass to G20 Finance Ministers and Central Bank Governors on the Global Economy and Health Agenda on July 15, 2022. The report discusses about the COVID-19 pandemic and now Russia’s invasion of Ukraine have caused a humanitarian and economic catastrophe. Recessions are likely in many countries. This will put heavy new burdens on fiscal deficits and debt markets. Ukraine is severely affected. The World Bank Group has been using all our tools to mobilize emergency financing for Ukrainians. More than 6 billion dollars of this financing has already been disbursed. The danger for other developing countries is acute due to inflation, currency depreciation, rising debt service costs, and the collapse of international reserves. These problems are severely constraining future growth and deepening inequality and fragility. The diversion of natural gas to Europe presents grave obstacles to developing country production of electricity, food, and fertilizer. Priority areas identified to complement work by existing institutions include disease surveillance; laboratory systems; emergency communication, coordination, and management; critical health workforce capacities; and community engagement.